Bionomics of Aedes mosquito species in three eco-epidemiological settings of Cameroon and their susceptibilities profiles to insecticides - Ms Bertille Djapoum; Ms Gisele Aurelie Foko Dadji; Mr Borel DJIAPPI-TCHAMEN; Mr Christophe ANTONIO-NKONDJIO (International Journal of Infectious Diseases)
Background: Arboviruses represent a serious concern in tropical/subtropical countries. In Cameroon, port cities and cities surrounded by forests constitute the main hot-spot of dengue and yellow fever. Due to the absence of effective treatments and vaccines against most arboviruses diseases, vector control remains the most effective measure to prevent further resurgence. To date, little is known about the bionomics of their main vectors Aedes aegypti and Aedes albopictus in such environments. This study aim to assess the bioecology, distribution and susceptibility profiles to insecticides of these vectors in three cities of Cameroon. Methods: Entomological surveys were undertaken from September 2021 to October 2022 in Bertoua (savanna area), Kribi (city port) and Sangmelima (forested area). Immature stages of Aedes spp. were collected by deeping and Stegomyia indexes were estimated. After emergence and morphological identification, F0 and F1 of Aedes aegypti and Aedes albopictus progeny will be used to assess the current phenotypic resistance status to the commonly used insecticides using WHO bioassays and mortality rates were assess according to the different insecticides tested. Results: A total 475 breeding sites in Sangmelima (41.47%), Kribi (33.47%) and Bertoua (25.05%) were identified. Tires and plastic containers were most abundant. A total of 2364 mosquitoes belonging to 4 genera and 9 species were collected. Aedes species recorded (1864) included Ae. albopictus (72%), Ae. aegypti (25.91%), and Aedes spp. (2.09%). These main vectors were present in all the study sites. Ae. albopictus was predominant in Sangmelima and Kribi while Ae. aegypti was mostly found in Bertoua. According to house indexes, transmission of dengue and yellow fever were high in Kribi and Bertoua. Ae. aegypti across study sites were found to be resistant to permethrin, deltamethrin and DDT, while Ae. albopictus was resistant to bendiocarb in Kribi and Bertoua. However, all these species were susceptible to malathion. Discussion: The study shows that Ae. albopictus and Ae. aegypti larvae live in a wide variety of breeding sites (Ngo et al., 2020), those species are largely distributed across the country(Tedjou et al., 2019). Ae. albopictus and Aedes aegypti were sensitive to organophosphates (malathion). These results are similar to previous studies (Kamgang et al., 2017). The tolerance and resistance observed could be due to the use of insecticides such as sprays and reminders, which are becoming more and more common(Nchoutpouen et al., 2019). Conclusion: The implementation of surveillance and control programmes for arbovirus vectors is urgent required in view of the increase in cases of arboviroses. To control arboviruses effectively, a targeted approach is needed to limit the spread of these vectors in our environment. This work is a contribution to vector control using ecological and susceptibility parameters with the aim of preventing a possible arbovirus epidemic in Cameroon.